Granuloma annulare – clinical presentation and therapeutic options - Chodorowska, Grażyna (Dermatology Review/Przegląd Dermatologiczny, 2012)
Granuloma annulare is a chronic skin disease of unclear aetiopathology. Various triggering factors are taken into consideration, including trauma, insect bites, antiviral vaccinations, viral and bacterial infections, UV exposure, coexisting immunological diseases or malignancies. The possible association with diabetes mellitus remains controversial and is considered insufficiently documented. Many data indicate that the delayed-type immunological response is involved in development of the disease, as well as the circulating immune complexes. Clinical presentation has many morphological variants and may cause diagnostic difficulties. Apart from 4 main forms (localized, generalized, subcutaneous and perforating), other clinical types can also be observed. The disease course is unpredictable, with a marked tendency for spontaneous resolution of skin lesions. There are many therapeutic options, both local and systemic, with a wide range of efficacy reported.